The effectiveness of schema-based education (the area of ​​selfmanagement and impaired or damaged performance) on academic self-efficacy and achievement motivation female students of the first secondary school - zohreh fotuhi; Hasan Asadzadeh; Ismail Sadipour; Fariborz Dortaj; Soghra Ebrahimighavam (مطالعات روانشناسی تربیتی)
This study aimed to determine the effectiveness of schema-based training in the area of autonomy and impaired performance on academic self-efficacy and achievement motivation among female middle school students. The statistical population included female students of the first period of middle school in Tehran province for the academic year 1400-1401. The research method was applied in terms of purpose and semi-experimental in terms of general design, with pre-test, post-test, and control group. Using a multi-stage cluster random sampling method, two schools were selected. From each grade in each school, 10 students were randomly chosen, totaling 60 students, who were then placed in experimental and control groups. Both groups responded to the academic self-efficacy questionnaires by Jerry Jing and Morgan (1999) and achievement motivation by Hermans (1977). The experimental group underwent 9 training sessions. The training package, based on schema, was developed by the researcher and had content and face validity, qualitatively and quantitatively determined by a panel of 10 experts with two validity coefficients: Content Validity Ratio (CVR) and Content Validity Index (CVI). Data analysis was performed using the multivariate analysis of covariance (MANCOVA) test. Results showed that schema-based training significantly and positively affects academic self-efficacy and achievement motivation (p<0.01).